Motivasi pelaku usaha mikro kecil dan menengah pada masa pandemi Covid-19 - Muhamad Azis Firdaus; Diah yudhawati; Titing Suharti; Rachmatulaily K.R (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to analyze the effect of perceptions of the pandemic and business conditions on the motivation of MSME actors. The analytical method is used by using the PLS structural equation model. The instrument used is an online questionnaire to MSME actors with the accidental sampling method. The instruments were distributed using gform, and 43 respondents were collected. Respondents come from various regions that are transmission areas for the spread of COVID-19. The study was conducted in the period January 2021 to August 2021. The results showed that there was no significant effect of the Perception of the Pandemic and Business Conditions on the Motivation of MSME Actors. This is indicated by the non-fulfillment of the model fit criteria from the structural equations formed. However, all constructs have valid and reliable indicators to be used in research. The results of this study illustrate that the motivation of business actors on the MSME scale is not influenced by pandemic conditions and business conditions during a pandemic. Respondents of MSME business actors have high motivation who continue to survive even during the pandemic